23-PUB: Reduction of Residual Lipid Risk in Patients with Type 2 Diabetes and Mixed Dyslipidemia Treated with a Fixed-Dose Combination of Atorvastatin/Fenofibrate - SANDER-PADILLA, JOSE G.; LUGO-SÁNCHEZ, LAURA A.; RIOS-BRITO, KEVIN F.; RODRIGUEZ-ROCANDIO, KARLA E.; ARGUEDAS, MARÍA M.; FLORES-HUANOSTA, DIANA; RODRIGUEZ-VAZQUEZ, ILEANA C.; GONZALEZ-CANUDAS, JORGE; ROMERO, YULIA (Diabetes (New York, N.Y.), 2024)
Introduction and Objective: The persistence of a high cardiovascular risk not dependent on LDL-C levels constitutes the residual cardiovascular risk of lipid origin (RLR). Lipid-lowering treatment does not always consider the modification of RLR. The present study aimed to evaluate the changes in RRL profile in patients with T2D and dyslipidemia treated with a fixed-dose combination (FDC) of Atorvastatin/Fenofibrate. Methods: A phase IIIb, randomized, prospective, double-blind, multicenter study in the Mexican population with diagnosis of T2D and mixed dyslipidemia. Patients were randomized to the Atorvastatin/Fenofibrate 20 mg/160 mg or Atorvastatin 20 mg once daily for four months. As part of the RLR evaluation, Triglycerides/HDL-C, residual cholesterol, Total cholesterol/HDL-C, and the triglycerides-to-glucose index (TyG) were estimated. Student's t-test and McNemar test (differences within groups) χ2, and independent samples Student's t-test were applied. Results: We included 65 patients with an average age of 56.8 ± 10.4 years. After two months of follow-up, there was a triglycerides reduction of -132.7 ± 145.3 mg/dL in the FDC group and of -68.7 ± 75.7 mg/dL with Atorvastatin therapy, while for the fourth month, the reduction was -138.3 ± 123.7 mg/dL and -60.5 ± 80.1 mg/dL, respectively. When evaluating RLR, both groups experienced a reduction in this profile, after 2 and 4 months of evaluation. However, when comparing the mean change reductions between groups of Triglycerides/HDL-C ratio (-3.9 vs -1.3, p=0.020), residual cholesterol (-19 vs -9.4, p= 0.018), and TyG (-0.7 vs -0.2, p=0.002) a superior outcome was found in FDC compared with the monotherapy group. Conclusions: Patients receiving Atorvastatin/Fenofibrate FDC had a better reduction than monotherapy in non-LDL cholesterol-dependent RRL markers, which translates to a decrease in overall cardiovascular risk for this treatment group.